Perlindungan Hukum Terhadap Anak Korban Kekerasan yang dilakukan oleh Orang Tua Wali - Jeheskel Retraubun; Sherly Adam; Carolina Tuhumury (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: A child is vulnerable to being a victim of abuse. The perpetrator could be the closest person, it is even possible that the child's parents themselves.Purposes of the Research: The purpose of this paper is to analyze and discuss the regulation of the rights of children victims of violence in the care of their parents guardians in the law as well as to analyze and discuss forms of special protection for children victims of violence by their parents. Methods of the Research: The type of research used is a normative legal research type (juridical normative), the problem approach used in this paper is a statutory approach (statute approach), concept analysis approach (analytical approach) and case approach (case approach). The materials used are primary legal materials and secondary legal materials. The collection of legal materials carried out in this study was carried out through library research, then analyzed using qualitative methods.Results of the Research: The regulation of legal protection for children victims of violence in the care of parents guardians in the law where the law of protection of children victims of violence committed. Forms of legal protection for children who are victims of violence carried out by parents and guardians provided by the government are coaching, mentoring, and social, health, physical and mental recovery. Then the form of special protection provided by the community and parents is to provide facilities and infrastructure, create a conducive atmosphere for children's growth and development, and nurture, nurture, educate and protect children.